Communication as a meta-theory for judgment and decision-making - Salmen, Karolin (2023)
Within the behavioral sciences, a substantial and influential body of research concerns judgment and decision-making (JDM). In general terms, this field investigates the process of decision-making, with its three core elements: evaluations or estimates of alternatives (judgments), how they are weighed according to personal characteristics (preferences) and integrated to pursue a course of action (choice; Fischhoff & Broomell, 2020). The psychological inquiry into JDM has been dominated by economic theories (mainly expected utility theory, Von Neumann & Morgenstern, 1944), social cognition (particularly dual process theories, e.g., Chaiken, 1980) and ecological approaches (e.g., Gigerenzer & Selten, 2002). Meanwhile, the investigation of communication processes only played a minor role in JDM theorizing, with some notable exceptions (e.g., Hilton, 1995). Spanning several phenomena and experimental paradigms central to JDM research, this thesis uses influential conceptualizations of communication introduced in Chapter 2 for novel theorizing about judgment and decision-making. In Chapter 3, seeing the research procedure as communication suggests that participants expect the researcher to communicate cooperatively and thus give responses corresponding to a classic cognitive illusion, the hindsight bias. Chapter 4 then focuses on competitive uses of communication by subtle means and how they can be used to discourage participants from following a testable, normative mental model for decision-making. Extending beyond the influence of cooperative and competitive pragmatics, Chapter 5 explores how a focus on the structure of the sign system, particularly that concepts may share the same cues, sheds new light on illusory correlations in judgments. In summary, this work furthers a communication perspective within the theoretical landscape of JDM research, in which social cognition, economic theories, and the ecological approach prevail.
Keywords: Hochschulschrift